Menstruation hygiene management and work attendance in a developing country - Astrid Krenz; Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2019)
Women in developing countries face challenges in terms of managing their menstrual hygiene. Oftentimes they do not possess the right means nor materials nor have access to the right facilities. Using a newly released dataset for Burkina Faso and propensity score matching, we provide for the first time evidence of a strong causal impact of advanced menstrual hygiene management on work attendance. Access to advanced menstrual hygiene management materials (disposable sanitary pads) reduces work absenteeism of women by about 21 percentage points. When we stratify the sample by religious affiliation, we find the treatment effect to be insignificant for Christian women and strong and significant for Muslim women.
Keywords: D10; I12; I14; J16; O12; 330; Menstrual Hygiene Management; Work Attendance; Period Poverty; Propensity Score Matching; Gender Inequality